2009
DOI: 10.1007/s10812-009-9255-2
|View full text |Cite
|
Sign up to set email alerts
|

Structural investigation of non-stoichiometric CuInS2 by 63Cu and 115In nuclear magnetic resonance

Abstract: Results of studies of non-stoichiometric CuInS 2 semiconductor by 63 Cu and 115 In nuclear magnetic resonance are presented. It was established that deviation of the composition from stoichiometry causes a quadrupolebroadened region of the NMR spectrum to change most. In this case a central peak whose shape is governed by the chemical shift anisotropy remains unaffected. NMR spectra reveal two types of structural distortions in the nearest surroundings of the In atoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Most of the 115 In SSNMR studies reported to date have largely focused on indium materials which are used (or have the potential to be used) as semiconductors or conductors. [33][34][35][36][37][38][39][40] Many of these studies report indium Knight shis, sometimes the quadrupolar parameters, and rarely, the chemical shi (CS) tensor parameters. In addition, most of these studies deal with indium materials in which In is in the +3 oxidation state and/or exists in highly symmetric environments.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the 115 In SSNMR studies reported to date have largely focused on indium materials which are used (or have the potential to be used) as semiconductors or conductors. [33][34][35][36][37][38][39][40] Many of these studies report indium Knight shis, sometimes the quadrupolar parameters, and rarely, the chemical shi (CS) tensor parameters. In addition, most of these studies deal with indium materials in which In is in the +3 oxidation state and/or exists in highly symmetric environments.…”
Section: Introductionmentioning
confidence: 99%
“…NMR spectra reveal 2 types of structural distortions in the nearest surroundings of the In atoms. 224 A pressure (P)-induced evolution of magnetism and superconductivity (SC) in a helical magnet CeRhIn 5 with an incommensurate wave vector Qi = ((1)/ (2),(1)/(2),0.297) through the 115 In NQR measurements under P was reported. Systematic measurements of the 115 In NQR spectrum reveal that the commensurate antiferromagnetism (AFM) with Qc = ((1)/(2),(1)/(2),(1)/ (2)) was realised above PmE1.7 GPa.…”
Section: Barium ( 137 Ba) (I = 3/2) the Local Ba Environment In B-bamentioning
confidence: 99%